Prognostic value of the absolute decrease of the N-terminal portion of B-type natriuretic propeptide in decompensated heart failure: secondary analysis of the CLUSTER-HF study - Paredes-Paucar, Cynthia (2022)
Objective. The purpose of this study is to determine the prognostic value of the absolute decrease in the N-terminal portion of pro-B-type natriuretic peptide (NT-proBNP) to prevent fewer clinical events, in the population of CLUSTER-HF (efficacy of ultrasound lung to guide therapy and prevent readmissions in heart failure). Materials and methods. This study was conducted in a subgroup of ninety-four patients with available NT-proBNP information at hospital discharge and prior to randomization in the CLUSTER-HF study. The primary objective of the study was to determine the prognostic value of absolute NT-proBNP decline below which fewer events of all-cause death, emergency room visits, and rehospitalization for heart failure at 180 days. Results. The absolute decrease in NT-proBNP below 3,350 pg/mL has a moderate discriminative capacity with AUC= 0.602, with a prognostic value in the combined event at 180 days (log-rank test, p=0.01). Also, according to the multivariable analysis, it is an independent marker of clinical events at 180 days OR 0.319 (0.102-0.995, p=0.04) above other clinical variables. Conclusions. An absolute decrease to 3,350 pg/mL of NT-proBNP or less at discharge from the hospitalization due to heart failure, was associated with fewer clinical events at 180 days.